2021
DOI: 10.5829/ije.2021.34.04a.17
|View full text |Cite
|
Sign up to set email alerts
|

Cogging Torque Minimization in Transverse Flux Permanent Magnet Generators using Two-step Axial Permanent Magnet Segmentation for Direct Drive Wind Turbine Application

Abstract: Transverse flux permanent magnet machines (TFPMs) are categorized as synchronous machines that benefit from having high value of torque density and capablity of accommodating high pole numbers. These characteristics make TFPMs suitable candidates for low-speed applications where high torque density value is requred such as direct drive wind turbine application. Despite the aforementioned advantages, TFPMs suffer from intrinsically high cogging torque value which is an important concern for wind turbine applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Wind power (G) [15,17,26,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. Direct-drive wind generators are part of the so-called variable speed wind turbines.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wind power (G) [15,17,26,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. Direct-drive wind generators are part of the so-called variable speed wind turbines.…”
Section: Applicationsmentioning
confidence: 99%
“…In the design process, it is essential to optimize the PMs arc ratio for the arrays: using the same PM pieces size would not be always the good option to reduce the cogging torque [64]. The axial PMs segmentation, also named PMs skewing, is another well-known technique for TFMs [16,77] that imitates the slot skewing of classic electric machines.…”
Section: Changing the Machine Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Different types of technology machines include axial and radial flux machines. Studies showed that axial flux machines (AFPM) have higher torque and power density (1)(2)(3), as well as efficiency (4-6). Axial field fluxswitching machines (AFFSPM) have limited torque density due to the location of PMs and coils, but still have higher torque and efficiency than radial flux machines and can reduce costs.…”
Section: Introductionmentioning
confidence: 99%
“…Two kinds of interior PM (IPM) and surface-mounted PM (SPM) machines are becoming candidates in highspeed applications. Figure 1 represents the most important advantages and disadvantages of the PMSGs [2][3][4][5][6]. In the last decade and along with the discovery of new PMs, these types of generators have drawn lots of attention, not only in academic papers but also in the power engineering world [7].…”
Section: Introductionmentioning
confidence: 99%